Algorithms for the Diagnosis and Treatment of Pulmonary Hemorrhage - Yu. V. Marchenkov; V. N. Yakovlev; I. Yu. Korzheva; V. G. Alekseyev; V. V. Moroz (Общая реаниматология)
Pulmonary hemorrhage is a severe complication that determines high mortality rates in various diseases and injuries. By reviewing the Russian and foreign literature and their many years’ experience, the authors depict current methods for the diagnosis and treatment of pulmonary hemorrhage. Action algorithms in relation to the etiology, pathogenesis, and degree of pulmonary hemorrhage have been composed for physicians of different specialties. Practical recommendations are given for current perioperative analgesic options during thoracotomy.